Myeloablative conditioning is well tolerated by older patients receiving T-cell-depleted grafts. - Novitzky, N; Thomas, V; Hale, G; Waldmann, H (2005)
Older age has been linked to increased transplant-related mortality from graft-versus-host disease (GvHD). Depletion of T cells from stem cell grafts seems to protect from complications of GvHD particularly in older patients. After myeloablative conditioning, patients with haematological malignancies received allogeneic grafts from HLA identical siblings. For GvHD prophylaxis, PBPC grafts were treated ex vivo with anti-CD52, and therapeutic doses of cyclosporin until day +90. Survival of patients younger or older than the population age median was analysed. In all, 62 consecutive patients with a median age of 42.5 years were studied. Death was procedure related in 17% and from relapse of malignancy in five. At a median, follow-up is 662 (7-2316) days, 74% survive disease free. The rate of haematopoietic recovery and treatment-related mortality was similar in both groups. A total of 73% of 30 individuals in the younger group and 75% (P=0.8) in the older cohort survive at a median follow-up of 444 and 806 days (P=0.4). GvHD occurred in 13% and was the only adverse factor for survival (P<0.04). Myeloablative conditioning is well tolerated up to the age of 59 in patients receiving T-cell-depleted grafts. This information is useful to more precisely select patients who would benefit most from reduced intensity conditioning schedules.